2008
DOI: 10.1093/jmedent/45.3.517
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mosquito Traps in Measuring Species Abundance and Composition

Abstract: Mosquito species abundance and composition estimates provided by trapping devices are commonly used to guide control efforts, but knowledge of trap biases is necessary for accurately interpreting results. We tested the hypothesis that commercially available traps (Mosquito Magnet-Pro, the Mosquito Magnet-X) would be significant improvements over the CDC Miniature Light Trap with respect to abundance, species diversity, and measures of recruitment in a wooded area of the Bronx Zoo in New York City, NY. The Mosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 11 publications
2
40
0
5
Order By: Relevance
“…Therefore, monitoring mosquito biodiversity is an important task in this area. Finally, our results suggest that although LTs sample most of the species in a mosquito community (Brown et al 2008), only the combination of several sampling methods provides a comprehensive description of a local mosquito faunal composition.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, monitoring mosquito biodiversity is an important task in this area. Finally, our results suggest that although LTs sample most of the species in a mosquito community (Brown et al 2008), only the combination of several sampling methods provides a comprehensive description of a local mosquito faunal composition.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have shown that Mosquito Magnet ® (MM) traps (American Biophysics Corporation, North Kingstown, RI) are more efficient than CDC light traps baited with CO 2 and/or octenol to collect mosquitoes (Brown et al 2008, Xu et al 2008, Hoel et al 2009, Dusfour et al 2010, Hiwat et al 2011a). Although it has been shown that the traps can be used for mosquito control and routine surveillance, the MM traps are marketed for the control of blood-seeking insects in residential areas (mosquitomagnet.com), although the traps have shown that can be used for mosquito control and routine surveillance (Pucci et al 2003, Brown et al 2008, Xu et al 2008, Kitau et al 2009.…”
mentioning
confidence: 99%
“…Although it has been shown that the traps can be used for mosquito control and routine surveillance, the MM traps are marketed for the control of blood-seeking insects in residential areas (mosquitomagnet.com), although the traps have shown that can be used for mosquito control and routine surveillance (Pucci et al 2003, Brown et al 2008, Xu et al 2008, Kitau et al 2009. The MM trap is battery operated and utilises CO 2 , one of the products of the catalysis of propane gas, as an attractant (Kline 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have determined that Aedes sp. were attracted at distances of 3 and 7 m from the CO 2 source (McIver & McElligott 1989) and that CDC-LTs placed 15 m apart act as independent traps (Brown et al 2008). Therefore, to avoid interference among traps, they were placed approximately 16 m apart.…”
Section: Methodsmentioning
confidence: 99%